Enhancing the enantioselective recognition and sensing of chiral anions by halogen bonding12. Issue 32 (29th March 2016) - Lim, Jason Y. C.; Marques, Igor; Ferreira, Liliana; Félix, Vítor; Beer, Paul D.
Abstract : Novel halogen bonding chiral ( S )-1, 1′-bi-2-naphthol-based receptor molecules significantly enhance enantioselective anion recognition and electrochemical sensing compared to their hydrogen bonding analogues. Abstract : Chiral halogen bonding ( S )-BINOL-based receptors are demonstrated to enhance the enantioselective recognition and sensing of chiral anions compared to their hydrogen bonding analogues. Computational studies attribute this behaviour to the strict linearity of halogen bonding (XB) and steric environment conferred by the XB donor groups bridged by the ( S )-BINOL motif.